We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
51
1
avatar

Solve for x:

(4^x+2^x-6)=0

 May 22, 2019
 #1
avatar+101086 
+1

4^x + 2^x - 6  = 0   factor  as 

 

(2^x  + 3) ( 2^x - 2) = 0

 

Setting the first factor to 0  and solving produces a non-real solution

 

For the second factor  we have

 

2^x - 2  = 0

 

And it's clear that x  = 1

 

 

cool cool cool

 May 23, 2019

11 Online Users

avatar
avatar